Next Generation of Smart Sensorless Drives for Sustainable Underwater Vehicles. Issue 21 (2016) - Allotta, Benedetto; D'Adamio, Pierluca; Nocentini, Lorenzo; Paolucci, Libero; Pugi, Luca
Abstract: Both Autonomous and Remotely Operated Underwater Vehicle play a key role in the development of offshore industrial installations assuring both cost and safety improvements in a very harsh environment. In order to improve performances, reliability and sustainability of underwater robotics, there is the need of a new generation of motors and drives devoted to this kind of applications. In this work authors focus their attention to most interesting aspect of the development of this new generation of products, introducing design examples and results of experimental activities performed on motors installed on Tifone, Marta and Feel Hippo AUVs